On Anti-Communist Falsifications of Social Structure in Lithuania - Skerstonas, Klemensas (Problemos, 1984)
The methodological principles of a scientific research into the social structure of a socialist society are revealed in the article. Basing on the theory of Marxism-Leninism a critical analysis of some anti-Communist views of Lithuanian reactionary emigrants on the social structure of socialist Lithuania is presented. Some deliberately false assertions by anti-Communists on the status of the working people and farmers in the socialist society are exposed in the article.